Synthetic biology of modular proteins. Issue 3 (4th May 2017) - Maervoet, Veerle E. T.; Briers, Yves
ABSTRACT: The evolution of natural modular proteins and domain swapping by protein engineers have shown the disruptive potential of non-homologous recombination to create proteins with novel functions or traits. Bacteriophage endolysins, cellulosomes and polyketide synthases are 3 examples of natural modular proteins with each module having a dedicated function. These modular architectures have been created by extensive duplication, shuffling of domains and insertion/deletion of new domains. Protein engineers mimic these natural processes in vitro to create chimeras with altered properties or novel functions by swapping modules between different parental genes. Most domain swapping efforts are realized with traditional restriction and ligation techniques, which become particularly restrictive when either a large number of variants, or variants of proteins with multiple domains have to be constructed. Recent advances in homology-independent shuffling techniques increasingly address this need, but to realize the full potential of the synthetic biology of modular proteins a complete homology-independent method for both rational and random shuffling of modules from an unlimited number of parental genes is still needed.